The naughty kid's handbook - "Green, Rod" (London; Dino Books, an imprint of John Blake Publishing Ltd, 2015)
Want to know how to get out of eating Brussels sprouts at Christmas? How to get out of kissing old Auntie Gladys? How to get dad to give you double pocket-money? The Naughty Kid's Handbook is the tool for you. Rod Green's handbook is filled with brilliant dodges, twists and pranks for little rascals. For every classic pre-teennightmare scenario, there is a genius solution. For every sleep over that needs a bedtime extension, there is a trick at hand. A perfect present for any high-spirited niece or nephew, this brilliantly illustrated book will be an endless source of fun for children and the parents who can be one step ahead if they do their homework! Parents needn't worry about their kids raising hell; this book is perfectly pitched. Rod has dreamed up all manner of funny, mischievous ideas but you'll find nothing unsafe or that could potentially cause any trouble for parents
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Funny Kids